Application of Physical Fitness Tests to Grade 7 Students at SMPN 5 Tanggul, Jember - Maharani, Regita Cahaya; Sulaiman, Ahmad (Universitas Muhammadiyah Jember, 2025)
This community service activity was carried out at SMPN 5 Tanggul, Jember, with the aim of providing training and measuring the physical fitness level of 7th grade students. Physical fitness refers to a person’s physical ability to perform daily activities without excessive fatigue while maintaining sufficient energy reserves. However, initial observations indicated that most students had relatively low fitness levels due to limited physical activity and a lack of adequate sports facilities at school. This program was implemented through the application of a physical fitness test consisting of ball throw and catch, sit-ups, standing jump, t-test, beep test, and measurements of height and weight. The results showed that the average fitness level of students was classified as moderate, with male students generally performing better than female students. Several problems arose during the program, including low student motivation, lack of initial understanding of test procedures, and limited school sports facilities. Through this program, students not only learned about their physical fitness levels but also gained direct education on the importance of maintaining physical fitness. This community service provided a valuable contribution through the application of experiential learning, where students actively participated in both the fitness assessment process and the reflection on their own physical condition. It is expected that this program will encourage students to adopt sustainable active lifestyles both at school and at home